Getting it - Sanchez, Alex (Simon & Schuster Books for Young Readers, 2006)
Hoping to impress a sexy female classmate, fifteen-year-old Carlos secretly hires gay student Sal to give him an image makeover, in exchange for Carlos's help in forming a Gay-Straight Alliance at their Texas high school.